Disruption of GluA2 Phosphorylation Potentiates Stress Responsivity - Ellis, Alexandra S. (Behav Brain Res, 2017)
Cocaine addiction is characterized by persistent craving and addicts frequently relapse even after long periods of abstinence. Exposure to stress can precipitate relapse in humans and rodents. Stress and drug use can lead to common alterations in synaptic plasticity and these commonalities may contribute to the ability of stress to elicit relapse. These common changes in synaptic plasticity are mediated, in part, by alterations in the trafficking and stabilization of AMPA receptors. Exposure to both cocaine and stress can lead to alterations in protein kinase C–mediated phosphorylation of GluA2 AMPA subunits and thus alter the trafficking of GluA2-containing AMPARs. However, it is not clear what role AMPAR trafficking plays in the interactions between stress and cocaine. The current study utilized a mouse with a point mutation within the GluA2 subunit c-terminus resulting in a disruption of PKC-mediated GluA2 phosphorylation to examine stress responsivity. Although no differences were seen in the response to a forced swim stress in naïve mice, GluA2 K882A knock-in mice exhibited an increased stress response following cocaine self-administration. Furthermore, we demonstrated that disrupting GluA2 phosphorylation increases vulnerability to stress-induced reinstatement of both cocaine seeking and cocaine-conditioned reward. Finally, GluA2 K882A knock-in mice exhibit an increased vulnerability to social defeat as indicated by increased social avoidance. Taken together these results indicate that disrupting GluA2 phosphorylation leads to increased responsivity to acute stress following cocaine exposure and increased vulnerability to chronic stress. These results highlight the GluA2 phosphorylation site as a novel target for the stress-related disorders.